GENERALIZATION OF WRITING A REVIEW PAPER: A CASE STUDY - Nagendra R (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This review paper provides a thorough synthesis of the existing research on topic of the review. The purpose of this study is to analyse and consolidate the current state of knowledge in this field, identifying key themes, trends, and gaps in the literature. Through a systematic review of peer-reviewed articles, books, and other scholarly sources, the paper examines specific aspects or subtopics, offering critical insights into main findings or themes. The review also highlights areas where further research is needed and discusses the implications of the findings for relevant fields, practices, or policies. Overall, this paper contributes to a deeper understanding of the subject matter and lays the groundwork for future studies in this area.